The Information Technology in Supply Chain Integration: Case Study of Reda Chemicals with Elemica - Waleed Rashad; Roman Gumzej (International Journal of Supply Chain Management, 2014)
The main objective of this article is to highlight the role of information technology in the supply chain, specifically in the B2B business automation, which is helping supply chains to achieve global integration. The benefits of this approach to improve the performance of supply chains are explained in this article through a case study of Reda chemicals using Elemica supply chain integration solutions for B2B automation. A qualitative approach is used to evaluate nodes in the supply chain integration and the results of the case study as well. The findings of this research are mainly comprised by two facts: (1) the information technology is essential for supply chain integrations and (2) it was established by our case study that using B2B business automation has led to significant improvement of the supply chain. The main contribution of this research lies in developing best practices of supply chain integrations using B2B automation. Keywords information technology, supply chain integration, B2B business, collaboration, logistics.